Pathways to Clean Energy Transition in Indonesia’s Electricity Sector with Open-Source Energy Modelling System Modelling (OSeMOSYS) - Pusanisa Paiboonsin; Gbemi Oluleye; Mark Howells; Rudolf Yeganyan; Carla Cannone; Simon Patterson (Energies, 2023)
Responding to the Paris Agreement and climate change mitigation, Indonesia aims to reach net zero by 2060 or sooner. Due to Indonesia’s dependence on coal and growing consumption, alternative sources of clean energy are imperative for meeting its rising energy needs and reducing energy-related greenhouse gas emissions to achieve the energy transition. This project aims to examine Indonesia’s opportunities and potential to achieve low carbon ambition in the energy sector and identify alternative pathways for the energy transition in Indonesia. In this study, the open-source energy modelling system (OSeMOSYS), which is a long-term energy system modelling tool, is employed to compare electricity generation, investment, and carbon dioxide emissions between business-as-usual and five alternative scenarios. Six scenarios, including business as usual, least-cost, two coal-phrase out and two net zero aligned with national climate targets and optimal scenarios, were simulated across different target years. The results show that the net zero (NZ) scenario is more cost-effective and emits fewer greenhouse gases than the other scenarios in meeting Indonesia’s future energy demand. However, achieving net zero by 2050 (NZ50) results in significantly lower CO2 emissions (10,134 MtCO2), which is less than half of the emissions in the net zero by 2060 (NZ60) scenario (16,849 MtCO2) at a similar cost (6229 and 6177 billion USD, respectively). This paper’s insights emphasise that large-scale renewable energy deployment and coal retirement are critical pathways to reaching carbon neutrality and achieving the energy mix transition.